Misquoting Jesus: The Story Behind Who Changed the Bible and Why - Bernas, Casimir (Cistercian studies quarterly, 2007)
The article reviews the book "Misquoting Jesus: The Story Behind Who Changed the Bible and Why," by Bart Ehrman.